2008
DOI: 10.1080/13576500701764124
|View full text |Cite
|
Sign up to set email alerts
|

Hand preference and hand performance: Cross-sectional developmental trends and family resemblance in degree of laterality

Abstract: The first aim of the study was to compare developmental trends in the degree of laterality (independent of direction) observed in two handedness tasks. The second aim was to assess family resemblance in the degree of laterality using the same two tasks. The sample was comprised of 186 left-handers and 302 right-handers aged from 6 to 66. Some of the sample were members of the same families. Bishop's card-reaching task was used to assess hand preference, and Annett's peg-moving task to assess manual performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
29
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 45 publications
6
29
0
3
Order By: Relevance
“…Kalisch (2006) also found that laterality moved towards a 50:50 ratio for left and right hand preference with increasing age. This complements a study by Doyen et al (2008) as they found there was an increase in difference of the left and right hands in younger individuals.…”
supporting
confidence: 71%
“…Kalisch (2006) also found that laterality moved towards a 50:50 ratio for left and right hand preference with increasing age. This complements a study by Doyen et al (2008) as they found there was an increase in difference of the left and right hands in younger individuals.…”
supporting
confidence: 71%
“…The TD group was comprised of participants from previously published studies (Carlier et al 2006a;Doyen and Carlier 2002;Doyen et al 2008) who were not biased for left-handedness; all TD group members were French. The three groups of genetic disorders were comprised of participants from previously published studies (Carlier et al 2006b;Gérard-Desplanches et al 2006) provided that they were in the age range set for the time of their assessment.…”
Section: Participantsmentioning
confidence: 99%
“…Ages ranged from 12 to 44 years at the time of their assessment. This age range was chosen primarily to avoid a strong age effect in the card-reaching task where the developmental curve of typical persons follows a linear increase from 3 to 11 years and a decrease after 12 years, with a plateau at adolescence and continuing throughout adulthood (Carlier et al 2006a;Doyen et al 2008). Second, we used this age range to obtain similar numbers of participants for the four groups (32-36 in each), with the exception of the group with the 22q11.2 deletion which had only 21 participants (see below).…”
Section: Participantsmentioning
confidence: 99%
“…Doyen et al. (2008) similarly demonstrated that adolescent children (ages 13–14) and adults reached across the body into contralateral space less often than preadolescent children (ages 7–12).…”
Section: Introductionmentioning
confidence: 93%